South-facing Jangha (wall) of the Mahanaleshwar Temple - Temples of India Project Team (Jio Institute, 2024)
The south-facing jangha (wall) of the Mahanaleshwar Temple is similar in scheme to that of the north and west-facing janghas. The bhadra (central projection) has the depiction of the Tripurantaka form of Shiva, the slender intermediary projections have surasundaris (celestial damsels), and the corner projections have dikapalas. On its left, the jangha connects to the kapili (the exterior wall portion that corresponds to the internal antarala or vestibule of the temple).